2021
DOI: 10.1038/s41598-020-80535-3
|View full text |Cite
|
Sign up to set email alerts
|

Neuromyelitis optica is an HLA associated disease different from Multiple Sclerosis: a systematic review with meta-analysis

Abstract: Neuromyelitis Optica and Multiple Sclerosis are idiopathic inflammatory demyelinating diseases of the central nervous system that currently are considered distinct autoimmune diseases, so differences in genetic susceptibility would be expected. This study aimed to investigate the HLA association with Neuromyelitis Optica by a systematic review with meta-analysis. The STROBE instrument guided research paper assessments. Thirteen papers published between 2009 and 2020 were eligible. 568 Neuromyelitis Optica pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 68 publications
0
7
4
Order By: Relevance
“…The HLA-DRB1*03 allele frequency is increased in classical AID, including diabetes mellitus type 1 33,34 , multiple sclerosis 41 , neuromyelitis optica 42 , systemic lupus erythematosus 43 , Graves' disease 44 and Sjögren's syndrome 35 , but we observed no association across IgG4-AID, only a decrease in studies on pemphigus. A similar difference could be found for HLA-DRB1*04, which is increased in classical AID diabetes mellitus type 1, rheumatoid arthritis and autoimmune hepatitis patients 38,45 , but decreased in IgG4-AID (MuSK, TTP and CIDP) -with the exception of pemphigus where a strong association was observed.…”
Section: Comparison Of Hla Associations Between Classical and Igg4 Autoimmune Diseasescontrasting
confidence: 68%
“…The HLA-DRB1*03 allele frequency is increased in classical AID, including diabetes mellitus type 1 33,34 , multiple sclerosis 41 , neuromyelitis optica 42 , systemic lupus erythematosus 43 , Graves' disease 44 and Sjögren's syndrome 35 , but we observed no association across IgG4-AID, only a decrease in studies on pemphigus. A similar difference could be found for HLA-DRB1*04, which is increased in classical AID diabetes mellitus type 1, rheumatoid arthritis and autoimmune hepatitis patients 38,45 , but decreased in IgG4-AID (MuSK, TTP and CIDP) -with the exception of pemphigus where a strong association was observed.…”
Section: Comparison Of Hla Associations Between Classical and Igg4 Autoimmune Diseasescontrasting
confidence: 68%
“…The HLA-DRB1*03 allele frequency is increased in classical AID, including diabetes mellitus type 1 (36,37), multiple sclerosis (44), neuromyelitis optica (45), systemic lupus erythematosus (46), Graves' disease (47) and Sjögren's syndrome (38), but we observed no association across IgG4-AID, only a decrease in studies on pemphigus. A similar difference could be found for HLA-DRB1*04, which is increased in classical AID diabetes mellitus type 1, rheumatoid arthritis and autoimmune hepatitis patients (41,48), but decreased in IgG4-AID (MuSK, TTP and CIDP) -with the exception of pemphigus where a strong association was observed.…”
Section: Comparison Of Hla Associations Between Classical and Igg4 Autoimmune Diseasescontrasting
confidence: 64%
“…), neuromyelitis optica(45), systemic lupus erythematosus(46), Graves' disease(47) and Sjögren's syndrome(38), but we observed no association across IgG4-AID, only a decrease in studies on pemphigus. A similar difference could be found for HLA-DRB1*04, which is increased in classical AID diabetes mellitus type 1, rheumatoid arthritis and autoimmune hepatitis patients(41,48), but decreased in IgG4-AID (MuSK, TTP and CIDP) -with the exception of pemphigus where a strong association was observed.4.3 HLA polymorphisms and the etiology of autoimmunityAutoimmune diseases are thought to have a multifactorial etiology with a cumulative effect of genetic predispositions and environmental triggers.…”
contrasting
confidence: 66%
“…Japanese and Chinese share the same HLA risk genes for NMOSD, namely HLA-DPB1*05:01 and HLA-DRB1*16:02 (Matsushita et al, 2009). Latin American studies (Alonso et al, 2018;Papais-Alvarenga, et al, 2021) disclose HLA-DRB1*03:01 and HLA-DRB1*10 alleles as a significant genetic association with NMOSD. Latin American studies have shown 80%-82.7% of the patients were women (Alonso et al, 2018;Soto de Castillo et al, 2020, Uribe-San Martin et al, 2017.…”
Section: Discussionmentioning
confidence: 99%